2005
DOI: 10.1038/sj.cgt.7700856
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis and HGF-cMET-elicited malignant processes in human hepatocellular carcinoma cells using adenoviral vector-mediated NK4 gene therapy

Abstract: NK4 is an hepatocyte growth factor (HGF)-antagonist and a broad angiogenesis inhibitor. NK4 gene therapy has confirmed antitumor efficacy on cancers with intact HGF-cMET signaling pathway. However, the feasibility to treat tumors in which the effect of the HGF-cMET signaling pathway is less unambiguous or may even be inhibitory on carcinogenesis, such as hepatocellular carcinoma (HCC) with NK4 needs further assessment. Therefore, we evaluated the effects of adenoviral vector-mediated expression of NK4 on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Most of them clearly show antineoplastic effects on various tumor cell types in vitro and in vivo such as decreased proliferation, migration and metastasis potential. Some of these experimental approaches such as adenoviral-mediated NK4 expression (Heideman et al, 2005) and antisense techniques have been successfully applied on HCC cells.…”
Section: Other Approachesmentioning
confidence: 99%
“…Most of them clearly show antineoplastic effects on various tumor cell types in vitro and in vivo such as decreased proliferation, migration and metastasis potential. Some of these experimental approaches such as adenoviral-mediated NK4 expression (Heideman et al, 2005) and antisense techniques have been successfully applied on HCC cells.…”
Section: Other Approachesmentioning
confidence: 99%
“…We found that tumor growth caused by subcutaneous injection of HepG2 shAbl cells was significantly reduced compared with that induced by HepG2 control cells (Figures 2b and c), which tumorigenesis has been demonstrated to be dependent on Met. 25 Similarly, we observed that c-Abl antagonists restrained Met-triggered tumor growth in vivo by following mice injected intraperitoneally with GTL-16 cells engineered for in vivo non-invasive bioluminescence imaging (Figure 2d). Imatinib treatment led to a reduction of tumor weight by 49%, and of nodule number by 64% (sizeo2 mm) and 61% (size42 mm) (Figures 2e and f).…”
mentioning
confidence: 93%
“…In particular, the insulin-like growth factor/IGF-1 receptor (IGF/IGF-1R), hepatocyte growth factor (HGF) [8] , Wnt [9] , transforming growth factor alpha/epidermal growth factor receptor (TGF-α/EGFR) [10] , and TGF-β/TGF-βR [11,12] pathways contribute to proliferation, anti-apoptosis, and invasive behavior of tumor cells. Midkine (MK) was first identified in embryonic carcinoma cells in early stages during retinoic acid-induced differentiation [13] .…”
Section: Introductionmentioning
confidence: 99%